Study of outbreak of pneumonia in AL-Nasiriya city in 2015 - Hlaihel, Abbas (University of Thi-Qar Journal of Science, 2015)
A retrospective study of 92 patients admitted to AL-Hussein teaching hospital diagnosed with pneumonia inwinter 2015 and 60 patients admitted in winter 2014 with pneumonia as control group. The age, sex and outcome [death or well] are recorded for each patients for both group, The presenting symptom for each patient in outbreak 2015 are recorded. Severity of pneumonia is assessed by CURB-65 and recorded for each patient, x-ray finding are recorded to patients in outbreak in2015 with result of sputum exam for gram stain and viral PCR in selected patients. Male to female ratio is 1:1 in outbreak of 2015 while it 0.6:1 in 2014 with significant difference between two groups and no sex difference in each group,The sex is not a risk factor for pneumonia except liogenella infection which more common in male. Severity of pneumonia is assessed by CURB-65 and result in 21 patients have score 3 and above [22%] and 10 have score 0 and 26 have score 1and 22[23%] patient have score 2.According to CURB-65 score ;36 patients no need to admission to hospital but other factor like co-morbid disease, for close up the compliance and response to treatment, and 22% have severe pneumonia need ICU admission and close monitoring.X-ray finding results in 40 patients show lobar consolidation, 22 patients showed bronchopneumonia pattern and 30 patients show diffuse interstitial infiltrate. Lobar opacity usually indicate bacterial infection while diffuse interstitial infiltrate usually nonbacterial mostly viral infection.